South Africa : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that South Africa's growth has slowed in recent years, specifically relative to other emerging markets. Although weak trading partners' growth contributed to the slowdown, increasingly binding structural constraints, such as protracted strikes and electricity constraints, have been important factors. Unemployment remains high at 25.5 percent. Notwithstanding expenditure discipline, the general government budget deficit was 4.5 percent of GDP in 2013, and public debt rose to 45 percent of GDP from 27 percent in 2008. The outlook is lackluster with considerable risks. Growth is projected to slow to 1.4 percent in 2014 and rebound only modestly to 2.1 percent in 2015 on improved industrial relations.